Updates and Comparative Analysis of the Mitochondrial Genomes of Paracoccidioides spp. Using Oxford Nanopore MinION Sequencing - Misas, Elizabeth; Gómez, Oscar M.; Botero, Vanessa; Muñoz, José F.; Teixeira, Marcus M.; Gallo, Juan E.; Clay, Oliver K.; McEwen, Juan G. (Frontiers in Microbiology, 2020)
The mitochondrial genome of the Paracoccidioides brasiliensis reference isolate Pb18 was first sequenced and described by Cardoso et al. in 2007, as a circular genome with a size of 71.3 kb and containing 14 protein coding genes, 25 tRNAs and the large and small subunits of ribosomal RNA. Later in 2011, Desjardins et al. obtained partial assemblies of mitochondrial genomes of P. lutzii (Pb01), P. Americana (Pb03) and P. brasiliensis sensu stricto (Pb18), although with a size of only 43.1 kb for Pb18. Sequencing errors or other limitations resulting from earlier technologies, and the advantages of NGS (short and long reads), prompted us to improve and update the mtDNA sequences and annotations of two Paracoccidioides species. Using Oxford Nanopore and Illumina read sequencing, we generated high quality complete de novo mitochondrial genome assemblies and annotations for P. brasiliensis (Pb18) and P. americana (Pb03). Both assemblies were characterized by an unusually long spacer or intron region (> 50 kb) between exons 2 and 3 of the nad5 gene, which was moderately conserved between Pb03 and Pb18 but not similar to other reported sequences, except for an unassigned contig in the 2011 assembly of Pb03. The reliability of the insert missing from previous mtDNA genome assemblies was confirmed by inspection of the individual Nanopore read sequences containing nad5 coding DNA, and experimentally by PCR for Pb18. We propose that the insert may aid replication initiation and may be excised to produce a smaller structural variant. The updated mtDNA genomes should enable more accurate SNP and other comparative or evolutionary analyses and primer/probe designs. A comparative analysis of the mtDNA from 32 isolates of Paracoccidioides spp., using the SNPs of the aligned mitochondrial genomes, showed groupings within the brasiliensis species complex that were largely consistent with previous findings from only 5 mitochondrial loci.